Anxiety, coping style and hopelessness during COVID‐19 pandemic: An Iranian population‐based study - Khodamorad Momeni; Yahya Salimi; Mohammad Reza Majzoobi; Arash Ziapour; Parisa Janjani (Health Science Reports, 2023)
Abstract Background and Aims The COVID‐19 pandemic has caused new conditions such as nationwide quarantine, a dramatic decrease in‐person interaction and an increase in death anxiety for governments and people. The pandemic of an unpredictable disease with no definite treatment can pose physical and psychological risks to individuals. The present study aimed to investigate the state of anxiety, coping styles, and hopelessness of people in the lockdown period and reopening in Iran. Methods In this national population‐based cross‐sectional study, a total of 1191 people who had access to social networks from all over Iran completed the anxiety, hopelessness, and coping style questionnaires online using the snowball sampling method. Analysis was conducted using Stata software version 12 (Stat Corp). The significance level was set at 0.05. Results The results of the study suggested that women experienced higher levels of anxiety than men, and, in stressful situations, women were more likely to use emotion‐focused coping styles, while men frequently used problem‐focused coping styles. The majority of participants reported moderate levels of anxiety and low levels of hopelessness (64.04%). The results of multiple linear regression show any level of anxiety mild (ß = 0.59, 95% confidence interval [CI]: 0.32–0.85), moderate (ß = 0.72, 95% CI: 1.36–1.08), and severe (ß = 2, 95% CI: 1.36–2.56) relative to the none anxiety significantly increase the hopelessness, Furthermore, showing a negative significant adjusted association with the problem‐focused coping style (ß = −0.06, 95% CI: −0.07 to −0.04), and a significant positive association with the emotion‐focused coping style (ß = 0.04, 95% CI: 0.02–0.06). Conclusion Our findings could be used to prevent psychological damage in societies and suggested addressing problem‐focused coping style, especially during a crisis, and providing people with preprepared mental health protocols at this pandemic.